Circular economy strategies for small domestic appliance design in China - Yi, Xianqin; Abdul Ghafar, Maszura; Aidi Hizami, Ales @ Alias (UiTM, 2024)
China is the world’s largest home appliance manufacturer, and the increased production of small domestic appliance (SDA) goods is leading to rising carbon emissions. Therefore, there is a need to upcycling SDA due to this phenomenon in China. The purpose of this research was to investigate the optimal circular economy (CE) strategies for SDA that would reduce the carbon footprint caused by this type of manufacturing. This study examined the current SDA design characteristics, usage features, CE concept, and circular product design. Then, based on a comprehensive examination, a circular product framework (CPD) and CE strategies for SDA design were recommended. The results indicate that when designers incorporate a CPD framework into the early stages of SDA design, product integrity could be enhanced, thus reducing carbon emissions. The research will benefit manufacturers by enabling improved SDA circularity, as well as supporting the reduction of e-waste and carbon emissions in China and worldwide.